METHODOLOGICAL ASPECTS AND RESULTS OF DETERMINING THE TECHNICALLY POSSIBLE HYDROPOWER POTENTIAL OF UKRAINIAN RIVERS (ON THE EXAMPLE OF THE DNIPRO RIVER BASIN) - OBODOVSKIY, Oleksandr; DANKO, Kostiantyn; POCHAIEVETS, Olena; KOROHODA, Nataliia; GREBIN, Vasyl (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. Diversification of electricity generation sources is gaining considerable attention in Ukraine today. This is especially true when the russian aggressors put out of commission the power generating capacities of thermal power plants and large hydroelectric power plants. In this context, the use of alternative (renewable) energy sources, in particular small hydropower, becomes important. That is why it is important to study the technically possible hydropower potential of rivers.Methods. The rationale for and the size of the technically feasible hydropower potential of rivers can be determined from the general scheme for determining the potential for rivers in Ukraine that we have proposed. For this purpose, an expert assessment of the main risks that may reduce the overall hydropower production was carried out.Results. It has been established that the largest percentage of losses of technically possible potential, relative to the total hydropower potential (THP), is inherent in the basins of the Pripyat, Stokhid and Samara rivers and ranges from 48–58.5 %. The slopes of river channels and waterlogging of their catchments play a key role here. The lowest rates of these losses are typical of such rivers as the Supiy, Irkliy, Stvyha and Uzh, and vary from 23 to 25 %. The priority here is losses caused by waterlogging and reclamation of floodplains.Conclusions. Taking into account all potential losses and risks, 226087 kW (39 %) of the total hydropower potential of the studied rivers can be considered suitable for use.
Keywords: technically possible hydropower potential; river energy; Dnipro River basin region; risk assessment; map